(untitled) (Medico Legal Update, 2019)
Hospital is required to provide effective and efficient health services in accordance with hospital service standards, including Surabaya Islamic Hospital. It actively carries out quality improvement services through managing the existing resources effectively and efficiently, evaluating and improving all installations, including inpatient service. This study aimed to perform efficiency effort of inpatient service for BPJS-Health participants at Surabaya Islamic Hospital, in the form of operational research. The samples were 30 inpatients of BPJS-Health participants. There were 8 waste found. Effort made to reduce the waste was by completing SIMRS with the data and information needed by the management for each work unit of inpatient service for BPJS-Health participants.